1988
DOI: 10.1111/j.1365-2141.1988.tb06198.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal membrane phospholipid organization in Plasmodium falciparum‐infected human erythrocytes

Abstract: The membrane phospholipid organization in Plasmodium falciparum-infected human erythrocytes was analysed by employing phospholipase A2 and Merocyanine 540 as external membrane probes. Both bee venom and pancreatic phospholipases A2 failed to hydrolyse phosphatidylserine in uninfected human red cells isolated from in vitro P. falciparum cultures. However, these enzymes under identical conditions readily degraded this aminophospholipid in P. falciparum-infected erythrocytes. Phosphatidylethanolamine hydrolysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
(11 reference statements)
2
13
1
Order By: Relevance
“…has been contradictory. For example, the results of Maguire et al [30] and Sherman, Prudhomme and Tait [31] agree with those of Joshi and Gupta [29,56] and Schwartz et al [57] in demonstrating PS exposure, but differ from the negative results of van der Schaft et al [58], Moll et al [59], and Taverne et al [60]. Indeed, Simoes et al [61] in commenting on these divergent findings suggested that it was excessive lysis, absence of glucose in the medium, and the use of buffers containing 100 mM KCl that resulted in "a dramatic change in phospholipid asymmetry".…”
Section: Discussionsupporting
confidence: 78%
“…has been contradictory. For example, the results of Maguire et al [30] and Sherman, Prudhomme and Tait [31] agree with those of Joshi and Gupta [29,56] and Schwartz et al [57] in demonstrating PS exposure, but differ from the negative results of van der Schaft et al [58], Moll et al [59], and Taverne et al [60]. Indeed, Simoes et al [61] in commenting on these divergent findings suggested that it was excessive lysis, absence of glucose in the medium, and the use of buffers containing 100 mM KCl that resulted in "a dramatic change in phospholipid asymmetry".…”
Section: Discussionsupporting
confidence: 78%
“…Lipid asymmetry of the membrane, maintained by an aminophospholipid translocase activity, is reduced in aged erythrocytes 41 or erythrocytes under oxidative stress. 42 Altered membrane PL organization, particularly a greater PS exposure on the outer surface of the membrane, has been reported in both IRBCs 2,43,44 and URBCs, 45,46 although not confirmed by others. 29,47 Oxidative stress induced by P falciparum might contribute to the loss of PS by changing the transbilayer organization of the membrane phospholipids and enhancing PS exposure on the outer surface.…”
Section: Discussionmentioning
confidence: 87%
“…1,28 It is important to draw attention at this point to the paucity and conflicting nature of data reported in the literature when whole infected RBCs (reflecting the separate contribution of the erythrocyte and the intracellular parasite itself) are studied and when total RBC populations of infected and uninfected cells are compared with no prior fractionation. 1,2,5,29,30 This variability has been attributed to different parasite species, level of parasitemia, developmental stages of the parasite, or purity of cell membranes. On the basis of our results, additional factors, which can be controlled by standardizing the experimental methodology, contribute to these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been previously reported (Browne & Hebbel, 1996) that thalassaemic patients' blood might contain RBC enriched with the adhesion molecule CD36 (which is absent in normal mature RBC). Both PS and CD36 can facilitate RBC/EC interaction, as elevated adhesion of RBC to EC observed in other RBC disorders, such as sickle cell anaemia and malaria, has been linked to elevated levels of PS (Joshi &Gupta, 1988) and CD36 (Wick &Eckman, 1996;McCormick et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been previously reported (Browne & Hebbel, 1996) that thalassaemic patients' blood might contain RBC enriched with the adhesion molecule CD36 (which is absent in normal mature RBC). Both PS and CD36 can facilitate RBC/EC interaction, as elevated adhesion of RBC to EC observed in other RBC disorders, such as sickle cell anaemia and malaria, has been linked to elevated levels of PS (Joshi &Gupta, 1988) and CD36 (Wick &Eckman, 1996;McCormick et al, 1997).Of special interest in the present study is the different adherence of TM and TI RBC, but the clari®cation of this question is hindered by the mixture of pathological and normal RBC in the blood of TM patients who are routinely treated with blood transfusion. The studies of BorenstainBen-Yashar et al (1993) and Browne & Hebbel (1996), which investigated RBC of transfused TM patients, indicate that TI RBC might have a higher level of PS and CD36 than TM RBC.…”
mentioning
confidence: 99%